Pasireotide for the Prevention of Pancreatic Fistula Following Pancreaticoduodenectomy: A Cost-effectiveness Analysis. Issue 1 (January 2017) - Goyert, Nik; Eeson, Gareth; Kagedan, Daniel J.; Behman, Ramy; Lemke, Madeline; Hallet, Julie; Mittmann, Nicole; Law, Calvin; Karanicolas, Paul J.; Coburn, Natalie G.
Abstract : Objective: To determine the cost-effectiveness of perioperative administration of pasireotide for reduction of pancreatic fistula (PF). Summary: PF is a major complication following pancreaticoduodenectomy (PD), associated with significant morbidity and healthcare-related costs. Pasireotide is a novel multireceptor ligand somatostatin analogue, which has been demonstrated to reduce the incidence of PF following pancreas resection; however, the drug cost is significant. This study sought to estimate the cost-effectiveness of routine administration of pasireotide to patients undergoing PD, compared with no intervention from the perspective of the hospital system. Methods: A decision-analytic model was developed to compare costs for perioperative administration of pasireotide versus no pasireotide. The model was populated using an institutional database containing all PDs performed 2002 to 2012 at a single institution, including data regarding clinically significant PF (International Study Group on Pancreatic Fistula Grade B or C) and hospital-related inpatient costs for 90 days following PD, converted to 2014 USD. Relative risk of PF associated with pasireotide was estimated from the published literature. Deterministic and probabilistic sensitivity analyses were performed to test robustness of the model. Results: Mean institutional cost of index admissions was 67, 417 and 31, 950 for patients with and without PF, respectively. Pasireotide was the dominant strategy, associated with savings of 1685, and a mean reduction of 1.5 days length of stay. Univariate sensitivity analyses demonstrated cost-savings down to a PF rate of 5.6%, up to a relative risk of PF of 0.775, and up to a drug cost of 2817. Probabilistic sensitivity analysis showed 79% of simulations were cost saving. Conclusions: Pasireotide appears to be a cost-saving treatment following PD across a wide variation of clinical and cost scenarios.